The Effect of Adding Cocoa Bean Shells (Theobroma cacao L.) on The Physicochemical and Sensory Characteristics of Instant Powder Drinks - Masayu Nur Ulfa; Fara Dita Nuraini; Muhammad Rizky Ramanda (University of Sultan Ageng Tirtayasa, 2026)
Cocoa is a leading commodity widely cultivated around the world, especially in Indonesia, which ranks as the fourth largest cocoa-producing country. Cocoa bean shells (Theobroma cacao L.) are a byproduct of cocoa bean processing, constituting about 10–16% of the dry weight of cocoa beans. Cocoa bean shells still contain bioactive compounds such as theobromine, caffeine, and polyphenols, which offer functional benefits. Additionally, cocoa bean shells have a distinctive aroma and flavor that are appealing for developing instant powdered beverage products. This study investigated the effect of adding cocoa bean shells on the physicochemical and sensory characteristics of instant powdered drinks. The concentrations of cocoa bean shells used were 0%, 10%, 20%, and 30%, analyzed using a Completely Randomized Design (CRD). Based on the research results, the concentration of cocoa bean shells addition had a significant effect (p0.05) on the moisture content parameter, which remained between 4.03–4.36%, influenced by the fiber content.